The effect of shock loading on the performance of a thermophilic anaerobic contact reactor at constant organic loading rate - Senturk, Elif; Ince, Mahir; Engin, Guleda Onkal (BMC, 2014)
The influences of organic loading disturbances on the process performance of a thermophilic anaerobic contact reactor treating potato-processing wastewater were investigated. For this purpose, while the reactor was operated at steady state conditions with organic loading rate of 5.5 kg COD/m(3) . day, an instant acetate concentration increase (1 g/L) was introduced to the reactor. During the shock loading test of acetate, it was observed that the overall process performance was adversely affected by all the shock loading, however, the system reached steady state conditions less than 24 hours of operation indicating that thermophilic anaerobic contact reactor is resistant to shock loading and be capable of returning its normal conditions within a short time period.
Keywords: Thermophilic; Anaerobic contact reactor; Shock loading; Recovery; Stability; WASTE-WATER TREATMENT; BIOHYDROGEN PRODUCTION; TREATMENT-PLANT; DIGESTION; BIOGAS; SLUDGE; STRENGTH; HYDROGEN; GLUCOSE; MANURE; Engineering; Environmental Sciences & Ecology